Kemampuan Menulis Teks Persuasif Siswa Kelas VIII SMP Negeri 2 Belopa - Isma, Sitti Nurmuthmainnah; Hamsa, Akmal; Idawati, Idawati (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the ability to compile text structure and use linguistic rules in writing persuasive texts of Class VIII students of SMP Negeri 2 Belopa. This research is quantitative, with a quantitative descriptive research type. This research involved Class VIII students of SMP Negeri 2 Belopa, totaling 28 students. The data collection technique in this study used persuasive text-writing assignment techniques. alysis technique that will be used in this research is descriptive statistics. The data analysis techniquthe dataat will be used in thsthesearch is descriptive statistics. The results of data analysis showed that: The ability to 56.50,se text structure in writing percategory,text obtained an average score of 56.50 which was in the quite capable category and the ability t60.89, linguistic rules in writing persuasive text obtained an average score of 60.89 which was in the quite capable category. Thus, the ability to write persuasive texts ofcategory,IIIents of SMP Negeri 2 Belopa is classified in the quite capable category so that it needs to be improved again so that students' writing skills can develop.